2012
DOI: 10.1182/blood-2012-02-412593
|View full text |Cite
|
Sign up to set email alerts
|

MHC I–associated peptides preferentially derive from transcripts bearing miRNA response elements

Abstract: MHC I-associated peptides (MIPs) play an essential role in normal homeostasis and diverse pathologic conditions. MIPs derive mainly from defective ribosomal products (DRiPs), a subset of nascent proteins that fail to achieve a proper conformation and the physical nature of which remains elusive. In the present study, we used high-throughput proteomic and transcriptomic methods to unravel the structure and biogenesis of MIPs presented by HLA-A and HLA-B molecules on human EBV-infected B lymphocytes from 4 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 50 publications
(100 reference statements)
6
69
1
Order By: Relevance
“…Comparison of the complete dataset with recent large-scale studies revealed that 81% of the peptides have not been reported before (SI Appendix, Table S2) (16)(17)(18). Remarkably, the unique peptides identified in this study have distinct sequence characteristics compared with literature data (SI Appendix, Fig S4).…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…Comparison of the complete dataset with recent large-scale studies revealed that 81% of the peptides have not been reported before (SI Appendix, Table S2) (16)(17)(18). Remarkably, the unique peptides identified in this study have distinct sequence characteristics compared with literature data (SI Appendix, Fig S4).…”
Section: Resultsmentioning
confidence: 62%
“…In contrast, biases in allele-specific peptide identification results could be directly translated to the known limitations of conventional peptide fragmentation techniques. This suggests that the outcome of HLA class I peptide identification studies that are based on CID (HCD) (16,18) or ETD (29) alone may only partially reflect the actual landscape of peptides presented at the cell surface. EThcD as the universal fragmentation method is therefore an attractive alternative to current MS sequencing technology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, although the proteasome was proposed as the main protease responsible for degradation of newly synthesized proteins, including DRiPs and SLiPs, autophagy and lysosomal proteolysis were mostly associated with degradation of long-lived, house-keeping proteins and whole organelles at the end of their functional lifecycles (64). Of interest is a recent study that suggests that a significant fraction of the MHC peptidome is derived from proteins whose transcripts have micro-RNA elements, which may affect the DRiPs production rates of the encoded proteins (69). The quantitative data provided in this study, points to the possible large involvement of such nonproteasomal pathways with the production of the HLA class I peptidome, including contributions from newly synthesized proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In cultured cells, upward to a third of the MHC peptidome was suggested to be derived from the latter. These rapidly degraded defective ribosome products (DRiPs) (4,9) were proposed to be produced by exotic mechanisms, such as downstream initiation (10), transcripts associated with specific microRNAs (11), premature termination of translation (12)(13)(14), short protein segments, produced by the pioneer round of translation (15) during the nonsense mediated decay (NMD) quality control of mRNA (16,17), and even out-of-frame translated segments of proteins (18). MHC peptides derived from newly synthesized proteins were also suggested to be produced by degradation of normal, fully functional polypeptides, which are the excess subunits of large protein complexes (19,20).…”
Section: Dripome | Immunopeptidome | Dynamic Silacmentioning
confidence: 99%